Mantle cell lymphoma: therapeutic options in transplant-ineligible patients. Issue 11 (19th September 2019) - Robak, Tadeusz; Smolewski, Piotr; Robak, Pawel; Dreyling, Martin
Abstract: Management of patients with newly diagnosed mantle cell lymphoma (MCL) depends on the age and fitness of the patient. For younger patients, the commonly accepted standard of care is a high-dose cytarabine-based induction chemotherapy followed by autologous stem cell transplantation (ASCT). In newly diagnosed patients with MCL ineligible for intensive therapy and ASCT, the standard-of-care has generally been R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone), followed by rituximab, maintenance. In recent years, bendamustine-based therapy has been increasingly adopted for older MCL patients and more recently, vincristine has been replaced by bortezomib in the R-CHOP combination as VR-CAP for previously untreated patients. Novel targeted agents now offer more promise than traditional chemotherapy or immunochemotherapy for both previously treated and untreated disease, and should also improve outcomes for older MCL patients. Here, we review standard therapies currently in use and novel agents that may soon be available for MCL patients and particularly for those unsuitable for ASCT.